2017
DOI: 10.1155/2017/5058609
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of Catalpol for Experimental Acute Focal Ischemic Stroke: Preclinical Evidence and Possible Mechanisms of Antioxidation, Anti‐Inflammation, and Antiapoptosis

Abstract: Neuroprotection is defined as using a therapy that affects the brain tissue in the still-viable ischemic penumbra to salvage or delay the infarction. Catalpol, the main active principle of the root of Radix Rehmanniae, was reported to have pleiotropic neuroprotective effects in neurodegenerative diseases including ischemic stroke. Here, we evaluated the neuroprotective effects of catalpol in experimental acute ischemic stroke. Studies on catalpol in animal models of acute ischemic stroke were identified from 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…Brain function and mental performance are affected by psychomotor speed and mental flexibility following damage or injury in the cerebral cortex capillaries; therefore, cigarette smoking can cause some changes in the vascular mechanism for blood flow and some physiological changes in the organs like brain (Mortazavi et al, 2010;Newhouse, Potter, & Singh, 2004). Thus, the smoking mechanism in patients with stroke and dementia has been well-defined through the effect of smoking on the vascular system (Cees De Groot et al, 2000;Raininko & Tilvis, 1993;Rogers, Meyer, Judd, & Mortel, 1985;Terborg, Bramer, Weiller, & Röther, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Brain function and mental performance are affected by psychomotor speed and mental flexibility following damage or injury in the cerebral cortex capillaries; therefore, cigarette smoking can cause some changes in the vascular mechanism for blood flow and some physiological changes in the organs like brain (Mortazavi et al, 2010;Newhouse, Potter, & Singh, 2004). Thus, the smoking mechanism in patients with stroke and dementia has been well-defined through the effect of smoking on the vascular system (Cees De Groot et al, 2000;Raininko & Tilvis, 1993;Rogers, Meyer, Judd, & Mortel, 1985;Terborg, Bramer, Weiller, & Röther, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is known to have several remarkable pharmacological effects, such as anti-asthma (Chen et al 2017), anti-diabetic (Bao et al 2016;Zhu et al 2016), hypoglycemic (Li et al 2014), and antitumor (Jin et al 2015;Liu et al 2017b;Wang and Zhan-Sheng 2018) properties. It has also been reported that catalpol acts as a neuroprotective agent for ischemic injury and neurodegenerative diseases (Tian et al 2006;Zhang et al 2007;Zheng et al 2017). In addition, its antioxidant effect can be achieved by blocking ROS production (Jiang et al 2008;Bi et al 2013;Cai et al 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Catalpol is an iridoid glycoside belonging the iridoid glycoside family and is highly abundant in Rehmannia glutinosa Libosch. Catalpol has been demonstrated to have neuroprotective, anti-apoptotic, anti-inflammatory, and anti-oxidative properties in animal and cell culture studies (Jiang et al 2015;Zheng et al 2017). Hu et al (2016) reported that catalpol inhibited apoptosis in cardiac myocytes via the mitochondrial-dependent caspase pathway.…”
Section: Introductionmentioning
confidence: 99%